The impact of cleaner production processes in enhancing the productivity of the organization: An analytical study of the opinions of a sample of workers in the Northern Cement Cooperative / Badoush Cement Plant Expansion (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to investigate and evaluate the impact of adopting cleaner production (CP) processes on enhancing the productivity of industrial organizations operating in [mention the sector or region the study focuses on, e.g., Nineveh Governorate, Iraq]. Driven by the global trend toward sustainability and the increasing pressure to reduce the environmental impacts of industrial activities, the study sought to identify and measure how cleaner production practices can contribute to improving operational efficiency and increasing productivity. The study relied on a descriptive analytical approach, and data was collected through a questionnaire distributed to managers and workers in the studied factory. The data was analyzed using SPSS for correlation and regression analysis.The study concluded that implementing cleaner production principles and processes represents an effective strategy not only for reducing the environmental impact of industrial organizations but also for enhancing their operational efficiency and increasing productivity. The study recommends that industrial organizations be encouraged to adopt cleaner production initiatives by providing incentives and raising awareness of their economic and environmental importance.
Keywords: Cleaner Production; Organizational Productivity; Badush Cement Plant